Microbiological Effect of Lemongrass Cymbopogon Citratus and Spearmint Mentha Spicata Essential Oils as Preservatives and Flavor Additives in Yogurt - Abed, Ibrahim Jabber; Hussein, Alyaa Razooqi; Abdulhasan, Ghusoon Ali; Dubaish, Anwar Neamah (Iraqi Journal of Science, 2022)
This study was designed to evaluate the antimicrobial effect of Cymbopogon citratus and Mentha spicata essential oils, separately and mixed, against the microorganisms in yogurt, as well as study the possibility of these essential oils (EO) as natural preservatives and flavors additives/enhancers in yogurt product. Yogurt samples were treated with lemongrass and spearmint EOin different concentrations (250, 500, 1000 ppm: 6250µg/50 ml yogurt, 12500 µg/50 ml yogurt and 25000 µg/50 ml yogurt respectively). The control and treated samples were preserved both at room (25°C) and refrigerator (5°C)  temperatures. In control, the contamination was observed through 2 weeks at 25°C and for about one month at 5°C. The samples treated with lemongrass and spearmint EOs (500pmm), the contamination showed up late, after 45 and 30 days at 25°C respectively. While at 5°C, the contamination appeared after 90 and 60 days respectively. The effect of lemongrass and spearmint EO, separately or mixed (synergistic effect), on the growth of fungi that was isolated from spoiled samples, was studied in different concentrations (125, 250, 500 ppm). Microbilogical examination was done in the control and treated yogurt samples. There was a significant difference (P≤ 0.05) between microbial spoilage (coliform, yeast and fungi) count during different periods of incubation which decreased in the samples treated with essential oils as compared with the control. The results of the percentage of growth inhibition revealed that lemongrass EO, around 80-100%, is the best in inhibiting the molds and yeasts causing yogurt damage as compared to the use of spearmint EO which was 27-60%, and the synergistic effect of about 35-39%. The results of the toxicity assay of the maximum effect of EO in vivo proved their validity for consumption when added both as preservative and flavor. The concentrations used for the dosage ranged from 250 ppm to 5000 ppm.